COMPARISON OF DATA ON NATURAL DRAINAGE CONSTRUCTION SURVEY WITH THE EXAMPLE ANALYTICALCALCULATIONS NEWLY BUILT NEIGHBORHOOD IN THE CITY OF OMSK - O. M. Rusanova (Вестник СибАДИ, 2017)
The inaccuracy of analytical formulas used in the calculations of drainage systems entails the error in the determination of the unknown quantities, such as the radius of the drainage depression and water flow to the drainage facilities. In this article, a comparison of the values of the water inflow to the reservoir drainage, obtained by calculation, the actual performance of the drainage system. It is shown how essential difference between the estimated and actual consumption value. The object of the research is bedded drainage under the residential buildings under construction in the district of Omsk, as well as the design values of linear drains expenses.